Pattern of Congenital Heart Disease in Children Presenting at Paediatric Cardiology Unit in Chattagram Maa Shishu-O-General Hospital, Chittagong (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Congenital Heart Disease (CHD) is the most common congenital problem in children. Early detection and proper management of congenital heart disease is very important to reduce mortality and morbidity. The purpose of this study was to find out the disease pattern of CHD among children in present situation in a center outside Dhaka.Methods: This study was conducted over a period from March 2016 to June 2017 prospectively and all patients with CHD was diagnosed by Color Doppler Echocardiography aging from 1st day of life to 12 years were included in the study.Results: Acyanotic CHD was most common among CHD. Atrial Septal Defect (ASD) was the commonest acyanotic congenital heart disease 100 (35.7 %) followed by Ventricular Septal Defect (VSD) 77 (27.5 %). Commonest cyanotic CHD was Tetralogy of Fallot (TOF) 9 (3.2 %). Only 25.36 % CHD were diagnosed during neonatal period whereas 54.64 % were diagnosed during the period of 29 days to completion of 12 months. Most of the patient (63.21%) were male.Conclusion: ASD was the commonest acyanotic CHD whereas TOF was the commonest cyanotic CHD. About 80% cases were diagnosed before 1 year of age. With the advancement of diagnostic facility and neonatal care, early detection of CHD is possible and treatment can be started at an earlier age.Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 40-43